Biofilm eradication and antifungal mechanism of action against Candida albicans of cationic dicephalic surfactants with a labile linker - Emil Paluch (Nature Portfolio, 2021)
Abstract Our research aims to expand the knowledge on relationships between the structure of cationic dicephalic surfactants—N,N-bis[3,3_-(dimethylamine)propyl]alkylamide dihydrochlorides and N,N-bis[3,3_-(trimethylammonio)propyl]alkylamide dibromides (alkyl: n-C9H19, n-C11H23, n-C13H27, n-C15H31)—and their antifungal mechanism of action on Candida albicans. The mentioned groups of amphiphilic substances are characterized by the presence of a weak, hydrochloride cationic center readily undergoing deprotonation, as well as a stable, strong quaternary ammonium group and alkyl chains capable of strong interactions with fungal cells. Strong fungicidal properties and the role in creation and eradication of biofilm of those compounds were discussed in our earlier works, yet their mechanism of action remained unclear. It was shown that investigated surfactants induce strong oxidative stress and cause increase in cell membrane permeability without compromising its continuity, as indicated by increased potassium ion (K+) leakage. Thus experiments carried out on the investigated opportunistic pathogen indicate that the mechanism of action of the researched surfactants is different than in the case of the majority of known surfactants. Results presented in this paper significantly broaden the understanding on multifunctional cationic surfactants and their mechanism of action, as well as suggest their possible future applications as surface coating antiadhesives, fungicides and antibiofilm agents in medicine or industry.